PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI A SDN 022 MUARA LANGSAT - Sartinem Sartinem (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Research on the use of STAD type cooperative learning model to improve student learning outcomes in learning mathematics in Class VI A SD Negeri 022 Langsat Estuary has been held in March to April 2015 at SD Negeri 022 Muara Langsat Sentajo Raya District, Kuantan Singingi Regency. The study was conducted on 22 students consisting of 14 male students and 8 female students. This classroom action research is conducted in 2 cycles, namely, cycle I and cycle II, where every action is observed through student activity observation and teacher activity observation sheet. From the research that has been carried out the results obtained that is on the cycle I average value obtained 63.2 and cycle II average score 83.6, the number of students who achieve success increased from the first cycle of 15 students or 68.18%, to be 20 students or 90.90% in cycle II. Increased student learning outcomes in line with the increase in student activity at the time of learning took place with 114 or 51.81% in cycles I and 190 or 83.36% in cycle II.